Development and validation of a constipation treatment toolkit for patients on hemodialysis. Issue 1 (16th August 2021) - Ng, Patrick; Lei, Katelyn; Teng, Lisa; Thomas, Alison; Battistella, Marisa
Abstract: Introduction: The cause of constipation is multifactorial and common problem for patients on hemodialysis. A lack of strong evidence on suitable treatment strategies means there is an unorganized approach to selecting therapies, which can exacerbate constipation or worsen symptoms. Clinicians and patients would benefit from a content and face validated treatment algorithm for treating constipation. In this study, our objective was to develop and content and face validate a constipation treatment toolkit for patients on hemodialysis, consisting of treatment algorithm, and patient information tools (pamphlet and video). Methods: Literature searches were performed to develop an initial toolkit using Lynn's method for developing content‐valid clinical tools. Content and face validity were evaluated as per Lynn's method for determining content validity; the algorithm was evaluated by Canadian nephrology clinicians, while patient information tools were evaluated by clinicians and patients. Components were rated on a Likert scale for content relevance and on a 5‐point scale for face validity. After each round, the content validity index (CVI) score was calculated and revisions were made based on feedback. Findings: A total of 23 clinicians and 15 patients were interviewed across three validation rounds. After three rounds, the treatment algorithm achieved content (overall CVI = 0.93) and face (91% agreement) validity. Our patient information tools achieved content and face validity (pamphlet overall CVI = 0.99, 85.5% agreement; video overall CVI = 0.99, 90.5% agreement). Discussion: A treatment algorithm and patient information toolkit for the treatment of constipation in patients on hemodialysis were content and face validated via expert review. Further research will be needed to ascertain the effectiveness and implementation of this toolkit.